1997
DOI: 10.2169/internalmedicine.36.322
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Centrifugal Leukocyte Apheresis for Corticosteroid-Resistant Active Ulcerative Colitis.

Abstract: Corticosteroids are effective in bringing about a clinical remission in patients with ulcerative colitis. However, in severely relapsed cases, corticosteroids are not always effective even whena high dosage is administered. In addition, the long-term use of corticosteroids often causes serious side effects. Therefore, an alternative treatment for active ulcerative colitis is necessary in order to avoid these clinical problems. In the present pilot study, the efficacy of leukocytapheresis using a centrifugal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…2 By processing 3 l of peripheral blood, corresponding to half of the body's blood, it is assumed that most circulating activated leukocytes can be removed and replaced by the naïve leukocytes from bone marrow or marginal pools. This phenomenon is also confirmed by the decrease in activated T cells, 3 the leukocytes expressing adhesion molecules such as L-selectin and integrins, 4 and the reactive oxygen species (ROS) 5 after apheresis. Based on the relative selectivity of removed leukocytes, the Aducolumn removes granulocytes and monocytes preferentially and the Cellsorba (LCAP) and centrifugal leukocytapheresis removes granulocytes/monocytes and lymphocytes in equal amounts, indicating that clinical effects of each apheresis may be derived from different mechanisms in addition to the total removal of Reprint requests to: Y. Kohgo proinflammatory cytokines, there is a possibility that the decrease of proinflammatory cytokines IL-1 and TNFα and inflammatory cytokines IL-8 and RANTES are involved by apheresis as reported in patients with rheumatoid arthritis.…”
Section: Why Is Leukocytapheresis Effective In Inflammatory Bowel Dismentioning
confidence: 79%
“…2 By processing 3 l of peripheral blood, corresponding to half of the body's blood, it is assumed that most circulating activated leukocytes can be removed and replaced by the naïve leukocytes from bone marrow or marginal pools. This phenomenon is also confirmed by the decrease in activated T cells, 3 the leukocytes expressing adhesion molecules such as L-selectin and integrins, 4 and the reactive oxygen species (ROS) 5 after apheresis. Based on the relative selectivity of removed leukocytes, the Aducolumn removes granulocytes and monocytes preferentially and the Cellsorba (LCAP) and centrifugal leukocytapheresis removes granulocytes/monocytes and lymphocytes in equal amounts, indicating that clinical effects of each apheresis may be derived from different mechanisms in addition to the total removal of Reprint requests to: Y. Kohgo proinflammatory cytokines, there is a possibility that the decrease of proinflammatory cytokines IL-1 and TNFα and inflammatory cytokines IL-8 and RANTES are involved by apheresis as reported in patients with rheumatoid arthritis.…”
Section: Why Is Leukocytapheresis Effective In Inflammatory Bowel Dismentioning
confidence: 79%
“…Leukocytapheresis has recently been used to induce remission in UC patients who fail to respond to corticosteroids [2,3,4,5,6,7,8]. Mechanisms by which leukocytapheresis induces clinical remission still are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some reports suggest that leukocytapheresis is associated with the remedial action on the cytokine network in a diseased state, returning it to a normal level via the inhibition of several proinflammatory cytokines and by enhancing production of inhibitory cytokines such as IL-4 and IL-10 [10, 11]. Three methods of leukocytapheresis have been used: centrifugation [3, 5, 8], filtration [2, 6], and passage through granulocyte and monocyte removal column [4, 7, 8]. A multicenter study of leukocytapheresis by centrifugation showed clinical improvement in 74% of 50 UC patients [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, UC cannot be considered to be a Th2-mediated disease without restriction, because production of the IL4 cytokine is diminished. The recognition of Tcells as being pivotal in the pathogenesis of UC has led to promising attempts to treat UC by removal of T-cells through therapeutic leukapheresis [44,45,46].…”
Section: T-cellsmentioning
confidence: 99%